An Impact of Destination Marketing and Smart Tourism Applications on Tourist’s Visit Intentions to Southern Africa - Steenkamp, Sherilee (University of the Witwatersrand, Johannesburg, 2023)
South Africa, a leading economy in Africa, faces challenges in its tourism sector despite its critical role in economic growth and employment. This study addresses the impact of destination marketing, focusing on digital marketing and user-generated content, and smart tourism applications like smart sightseeing, on tourists' visit intentions in Southern Africa. Using a quantitative approach with an online questionnaire administered to 402 international participants, the research investigates how these factors influence perceived destination image, attitude, and subjective norms. Findings reveal that digital marketing significantly enhances perceived destination image, which in turn positively affects tourists' attitudes. Familiarity also plays a crucial role in shaping attitudes, supporting existing theories on mere exposure. Moreover, attitude directly correlates with visit intention, supporting the Theory of Reasoned Action and the Theory of Planned Behaviour. Subjective norms moderate this relationship, underscoring the influence of social approval on tourists' behavioural intentions. This study contributes insights into enhancing destination marketing and smart tourism strategies to strengthen Southern Africa's tourism sector.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Destination marketing; Smart sightseeing; Perceived destination image; Familiarity, attitude; UCTD; SDG-8: Decent work and economic growth